KAJIAN PEMUPUKAN KELAPA SAWIT (Elaeis guineensis Jacq) MENGGUNAKAN METODE SEMI MECHANICAL MANURING (SMM) - Siahaan, Megawati; Wagino, Wagino; Tarigan, Lui Jemtanta (Agro Estate, 2023)
Fertilizing is one of the important activities in palm oil cultivation which is high cost, because of that we must find ways to increase its effectivity and efficiency. Semi Mechanical Manuring (SMM) is a breakthrough in fertilizing which used in Kebun Bekiun, PT. Langkat Nusantara Kepong. This Research is held in Divisi III, Kebun Bekiun, PT. Langkat Nusantara Kepong. Qualitative Description is used as research method with describe procedure operation and administration of this method. This Research shows that Kebun Bekiun has done 5 principles in fertilizing which are kind, method, time, place and dosage has been exactly by field assistant, plantation manager and head of plantation. SMM is mini truck modified to increase efficiency and effectivity of fertilizing. SMM is designed to cross all tracks in oil palm plantations and process of fertilizing will be faster than manual application and easier to control the field.  Price of fertilizer using SMM was Rp. 46/Kg cheaper than manual application. When the research was doing, this plantation needed to spread 6000 kg fertilize which were been broad to 107.989 palms with 2 kgs each palm; it means this plantation has efficiency Rp. 9.934.988,-/application. The efficiency come from the decrease of man power to spread the fertilize.